Water-pipe smoke condensate increases the internalization of Mycobacterium Bovis of type II alveolar epithelial cells (A549) - Mortaz, Esmaeil; Alipoor, Shamila D.; Movassaghi, Masoud; Varahram, Mohammad; Ghorbani, Jahangir; Folkerts, Gert; Garssen, Johan; Adcock, Ian M. (BMC pulmonary medicine, 2017)
Background Tuberculosis (TB) is a major global health problem, and there is an association between tobacco smoke and TB. Water pipe smoking has become an increasing problem not only in Middle Eastern countries but also globally because users consider it as safer than cigarettes. The presence of high levels of toxic substances in water-pipe smoke may be a predisposing factor that enhances the incidence of pulmonary disorders. For example, uncontrolled macropinocytosis in alveolar epithelial cells following exposure to water-pipe smoke may predispose subjects to pulmonary infection. Here, we studied the effects of water-pipe condense (WPC) on the internalization of Mycobacterium Bovis BCG by macropinocytosis in the alveolar epithelial cell line A549. Methods A549 cells were exposed to WPC (4 mg/ml) for 24, 48, 72 and 96 h. Cell viability was studied using the methyl thiazolyldipenyl-tetrazolium bromide (MTT) reduction assay and proliferation by bromodeoxyUridine (BrdU) incorporation. Cells were exposed to FITC-Dextran (1 mg/ml) (as a control) and FITC-BCG (MOI = 10) for 20 min at 37 ° C before cells were collected and the uptake of BCG-FITC determined by flow cytometry. Similar experiments were performed at 4 ° C as a control . The Rho-associated protein kinase (ROCK) inhibitor Y-27632 (1 μM) was used to assess the mechanism by which WPC enhanced BCG uptake. Results WPC (4 mg/ml) increased the uptake of BCG-FITC after 72 (1.3 ± 0.1 fold, p < 0.05) and 96 (1.4 ± 0.05 fold, p < 0.05) hours. No effect on BCG-FITC uptake was observed at 24 or 48 h. WPC also significantly increased the uptake of FITC-Dextran (2.9 ± 0.3 fold, p < 0.05) after 24 h. WPC significantly decreased cell viability after 24 (84 ± 2%, p < 0.05), 48 (78±, 3%, p < 0.05), 72 (64 ± 2%, p < 0.05) and 96 h (45 ± 2%, p < 0.05). Y-27632 completely attenuated the increased uptake of BCG by WPC. Cell proliferation showed a decreasing trend in a time-dependent manner with WPC exposure. Conclusion WPC exposure increased epithelial cell endocytosis activity and death as well as enhancing their capacity for macropinocytosis. Our in vitro data indicates possible harmful effects of WPC on the ability of lung epithelial cells to phagocytose mycobacterium.